An Ochratoxin A Electrocatalytic Sensor Based on Electron Mediator Decorated Nanoalloy Biomimetic Enzyme Coupling with Label-Free Hair Aptamer. Issue 3 (4th March 2021) - Wang, Xiaoying; Lv, Liangrui; Chen, Qingqing; Xu, Mingming; Yu, Bingjia
Abstract : An electrocatalytic sensor based on electron mediator toluidine blue (Tb) decorated PtPd nanoalloys (PtPdNAs) biomimetic enzyme coupling with label-free hair aptamer (HA) for OTA detection was successfully constructed. In this work, label-free HA was designed containing anti-OTA aptamer sequence (APT) and complementary sequence (cDNA) of report DNA (rDNA). rDNA and Tb joint decorated PtPdNAs (Tb-PtPd-rDNA) was used as a signal probe. The peroxidase-like activity of the PtPdNAs combined with the synergistic catalysis of the Poly 3, 4-ethoxylene dioxy thiophene-AuNPs (PEDOT-AuNPs) coated glass-carbon electrode (PE-Au/GCE) resulted in strong catalytic current of Tb and eventually significantly improved the sensitivity of the sensor. The response current had a good metrological-signal relationship with OTA concentration from 0.1 pg ml -1 to 0.1 ng ml -1, and the low detection limit of 0.05 pg ml -1 was obtained. Meanwhile, the proposed sensor exhibited a good correlation with HPLC when it was applied for OTA detection in red wine samples. The strategy broadens the design of catalytic sensor and can be applied to the detection of other small molecules.